Interface of Insurance and Economic Growth: Nigerian Experience - Adetunji, Adedokun Lateef; Nwude, E. Chuke; Udeh, Sergius N. (International Journal of Economics and Financial Issues, 2018)
The study aims to confirm the existence of positive and significant relationship between insurance penetration/activity and economic growth in Nigeria. Applying Ordinary Least Square model on Nigerian time series data for the period 1996-2015 reveals that insurance industry makes positive and significant contribution on Nigeria's economic growth. Based on the findings, it is recommended that government should implement economic policies capable of stimulating insurance industry activity such as the enforcement of the statutory insurances; insurance industry stake-holders should improve the insurance image laundry and market awareness activity by promoting systematic educational campaign in the media and among the general public. Keywords: Insurance, economic growth, Nigeria, insurance premium, insurance investment, emerging economy. JEL Classifications: C32, E31, E37, F31, O52